Physicochemical Properties, Antioxidant Capacity, and Consumer Acceptability of Ice Cream Incorporated with Avocado ( Persea Americana Mill.) Pulp - Jutamas Moolwong; Worasaung Klinthong; Thanida Chuacharoen (Polish Journal of Food and Nutrition Sciences)
Avocado pulp is low in sugar contents but quite high in dietary fiber, nutrients, and phytochemicals with potential health benefits. In this study, the avocado pulp was incorporated into ice cream. The effects of replacing milk fat with avocado on the physical and chemical properties of ice cream and consumer acceptability were evaluated. Milk fat-based ingredients of the ice cream were partially replaced with avocado pulp at ratios of 10, 20, and 30% (w/w). All ice creams were subjected to physical and chemical analyses and were evaluated in sensory acceptability tests. Replacing milk fat with avocado pulp significantly reduced moisture content, protein, and fat content, while it increased the carbohydrate (3.70 to 7.91 g/100 g) and crude fiber content (0.39 to 1.38 g/100 g). A higher content of avocado pulp caused a reduction in overrun and retarded the melting rate due to the effect of high fiber content. Increased viscosity and hardness were observed. The ice cream with the highest avocado pulp content had approximately 3-fold higher total phenolic content determined by the Folin-Ciocalteau method and 2-fold higher antioxidant capacity evaluated as DPPH• and ABTS•+ scavenging activity, and ferric reducing antioxidant power compared to that of the control. Sensory evaluation showed the 20% (w/w) avocado pulp was the suitable ratio for incorporating in the ice cream, which showed a good level of overall acceptability. Thus, our results suggest the potential use of avocado pulp to replace milk fat in frozen dairy products.